Doing Research with Vulnerable Populations: The Case of Intravenous Drug Users - Murdoch, Blake; Caulfield, Timothy (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2016)
This review article considers ethical concerns when doing research on potentially vulnerable people who inject drugs (PWID) in a Canadian context. The Tri-Council Policy Statement: Ethical Conduct for Research Involving Humans broadly addresses many of the traditional ethical principles of research on vulnerable persons, but does so at the cost of clarity and precision. Vulnerability is contextual rather than absolute. When doing research with vulnerable persons, informed consent should be obtained from an independent person, and comprehension should be checked using questioning. Participants can be vulnerable due to many factors, including addiction, chronic disease, socioeconomic and racial status, and lack of education. The ability of PWID to give informed consent can be compromised by undue influence or intoxication, but existing research shows that neither the mode nor the magnitude of compensation has a significant effect on new rates of drug use. Compensation can also help dispel the therapeutic misconception. Intoxication rather than undue influence is the main concern when obtaining informed consent from PWID. The stigmatization of PWID as incapable of consent should be avoided. Paternalistic exclusion from research can harm PWID and exacerbate their vulnerability by reducing our knowledge of and ability to specifically treat them. As such, we must collect better data about the effects of research ethics policies. Studies to this effect should focus on experiences, perspectives and needs of potentially vulnerable research participants. Research ethics boards in Canada should adopt an evidence-based approach when applying discretionary power to proposals for clinical research.